2022
DOI: 10.12775/jehs.2022.12.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A sense of coherence and styles of coping with stress of students of medical and non-medical universities

Abstract: The article relates to a sense of coherence and styles of coping with stress in a group of students of medical and non-medical universities. In the first part, a brief characteristics of the specifics of studies and future student work from both types of universities were presented. The issue of a sense of coherence and coping with stress in research was approximated closer. The study used a life orientation questionnaire (SOC-29) examining the sense of coherence and a questionnaire of coping in stressful situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Thus, being able to recognize stressful situations, mobilize resources to promote effective coping, and find solutions to resolve situations and difficulties, in order to have a better quality of lifestyle and health. Jurczyszyn A. and Zdziarski K. [ 49 ], showed in a study on sense of coherence among 145 Polish university students a slightly lower sense of coherence among students studying medicine compared to a group from non-medical universities, in contrast to our study, which found no statistically significant difference between medicine and the other areas searched.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, being able to recognize stressful situations, mobilize resources to promote effective coping, and find solutions to resolve situations and difficulties, in order to have a better quality of lifestyle and health. Jurczyszyn A. and Zdziarski K. [ 49 ], showed in a study on sense of coherence among 145 Polish university students a slightly lower sense of coherence among students studying medicine compared to a group from non-medical universities, in contrast to our study, which found no statistically significant difference between medicine and the other areas searched.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, being able to recognize stressful situations, mobilize resources to promote effective coping, and find solutions to resolve situations and difficulties, in order to have a better quality of lifestyle and health. Jurczyszyn A. and Zdziarski K. [49], showed in a study on sense of coherence among 145 Polish university students a slightly lower…”
Section: Plos Onementioning
confidence: 96%